The Level Of Basic Football Skills In The Youth Category Of The Football School (SSB) Adolina Perbaungan In 2024 - Rusdi, Rusdi; Helmi, Boby (Journal of Football Research, 2025)
This study aims to determine the level of basic football skills in the Adolina Perbaungan Football School (SSB) Youth Category in 2024. This research is descriptive research using the survey method. Data collection techniques in this study using tests and measurements. The population is 20 people and the sample size is 20 people. Based on the results of the study, it can be seen that the Level of Basic Football Skills in the Adolina Perbaungan Football School (SSB) Youth Category in 2024 is in the ‘less’ category with a percentage of 10%, the ‘medium’ category with a percentage of 55%%, the ‘good’ category with a percentage of 35%. Based on these results it is concluded that the Level of Basic Football Skills in the Adolina Perbaungan Football School (SSB) Adolescent Category in 2024 is in the ‘medium’ category with a percentage of 55%